Alatan audit dokumentasi jaminan kualiti IPTA di FSKSM - Mohammad, Noraini (2006)
Audit Documentation Tool for IPTA Quality Assurance System is developed with the purpose to assist the process in documenting the IPTA Quality Assurance at FSKSM. The main problem with current system is that it is difficult to manage the documents and information effectively and systematically. The features of audit documentation had been applied as the guideline and support in preparing documents with a good quality. These features are planning, implementing, reports monitoring, feedback and updating the information. Audit Documentation Tool for IPTA Quality Assurance System is developed by using the audit documentation’s features in order to the documentation process of IPTA Quality Assurance at FSKSM. The system is developed using prototype methodology and Structured System Analysis Development Methodology (SSDAM). In this study, PHP is chosen as the programming language and MySQL as the database management system. It is hoped that this system will benefit the Faculty Committee Member and will assist them in documenting Academic Quality Assurance.